Corporate Social Responsibility Implementation by State-Owned Enterprises: Economic Impacts in Makassar, Indonesia - Syachbrani, Warka; Paramita, Ahsani (Technium Business and Management, 2024)
This study aims to determine of the implementation of Corporate Social Responsibility by The State-owned Enterprise in Makassar. This study was conducted research on programs, activities, and regulations of the company, then compared with statements of local communities who are directly involved or receive benefits from company existence. Data were obtained from documentation and interviews from both PT Industri Kapal Indonesia and community. Results of this study shows that State-owned Enterprise has implemented Corporate Social Responsibility. In this case, the Company has carried out various kinds of social programs and activities for the environment and the community. Its as seen also from the results of interviews with employees, and residents around the company. Furthermore, the study shows positif impact to the economic conditions to the community.